Antimicrobial Compounds from the Rihzomes of Sansevieria hyacinthoides (Bangladesh Journal of Scientific and Industrial Research, 2011)
Three known compounds were isolated from the n-hexane extract of the rihzomes of Sansevieria hyacinthoides, they were two steriods; β- sitosterol (1) and daucosterol (2), and a flavonoid; isokaemferide (3). The structures of the compounds were elucidated on the basis of NMR spectral analysis as well as comparison with available data in the literature. All extracts and the three pure compounds were evaluated for their antimicrobial activity. The compounds showed moderate activity against Bacillus subtilis, Stapylococcus aureus, Salmonella typhi and Candida albicans. Key words: Sansevieria hyacinthoides; Antimicrobial activity; Infectious diseases; Flavonoid; Steriods DOI: http://dx.doi.org/10.3329/bjsir.v46i3.9038 BJSIR 2011; 46(3): 329-332